Konsep Pendidikan dalam Keluarga, Sekolah, dan Masyarakat Dalam Kerangka Pendidikan Nilai dan Karakter (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to understand and analyze the role and contribution of each educational environment of family, school, and community in instilling moral values ​​and forming the character of students in an integrated and sustainable manner. This qualitative study uses library research, the research method is carried out by collecting and analyzing various relevant written sources. These sources can be in the form of scientific journals, books, online articles, research reports, or official publications that discuss the concept of education in families, schools and communities within the framework of value and character education. The results of the study show that: 1) Value and character education is most effective when there is synergy between family, school, and community; these three environments complement each other in forming the personality and morals of students. 2) Lack of consistency in instilling values ​​between the three environments can cause value confusion in children, so intensive communication and cooperation are needed between parties to achieve the goals of complete character education. Why impact why the results are like that because family, school, and community have an important role in shaping children's character. If all three are in harmony and support each other.